PENGEMBANGAN MODUL BERBASIS EBOOK UNTUK MENINGKATKAN PENGETAHUAN BAHAYA MEMBOLOS SISWA - Jundi Pratama; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to develop a feasible and effective electronic module (E-Module) on the harmful behavior of skipping class to increase students' knowledge of the harmful effects of skipping class. This module is designed to facilitate guidance and counseling teachers when providing guidance and counseling services and attract students to learn how to avoid and know the impact of skipping school. This research uses the R&D (Research and Development) method with the 4D model with its stages, namely define (defining), design (designing), development (developing), dissemination (disseminating). The data collection technique carried out in this research and development is through a need assessment on a sample of 101 class X students of SMK PGRI 1 Kota Serang, the results obtained are as many as 24 students or 23% are in the category of not understanding and 21 students or 20% of them are in the category of very not understanding the impact of skipping class. Then, the results of the need assessment are poured into the product in the form of a module and product validity testing is carried out to media and material experts, linguists and practitioner experts. The trial was carried out providing services in accordance with those contained in the module by guidance and counseling teachers to 25 students, the results were 48.00% or 12 students were in the understanding category and 52.00% or as many as 13 students were in the very understanding category. N-Gain percent of the trial amounted to 80.94% d.Keywords: Module, Truancy Behavior, Dangers of Truancy.